Talent Retention: A Mediator of the Relationship Between Talent Management Strategies and Succession Planning - Poonam Jindal (Universiti Sains Malaysia, 2021)
Succession planning is becoming a focus point for discussion in business world as very few organisations are prepared with their successors for occupying the position as and when it is needed. With special reference to Indian pharmaceutical companies, where talent is critical and rare in nature, this becomes a more crucial requirement. This paper, by integrating theory of Internal Labour Market (ILM), deals with the relationship among talent identification (TID), talent development (TD), talent retention (TR), and succession planning in Indian pharmaceutical companies. A survey method was used for collecting the response of senior level managers of pharmaceutical companies located in Hyderabad, India, and the hypothetical model and structural relationships were tested via structural equation modelling (SEM). The findings of the research present that TR plays a role of mediator in the relationship of TID, TD and succession planning in organisations. This study helps pharmaceutical companies to be future ready for succession planning by using their regular talent management strategies skilfully. This study beautifully develops an empirical relationship between TID, TD, and succession planning with the mediating effect of TR. Research also brings out the theoretical importance of ILM theory. This, as per best of researchers’ knowledge, was not presented in earlier research on talent management or on succession planning.